Investigation of OMNIgene·SPUTUM performance in delayed tuberculosis testing by smear, culture, and Xpert MTB/RIF assays in Uganda - C.D. Kelly-Cirino; E. Musisi; P. Byanyima; S. Kaswabuli; A. Andama; A. Sessolo; I. Sanyu; J. Zawedde; P.S. Curry; L. Huang (Springer, 2019)
OMNIgene·SPUTUM (OM-S) is a sample transport reagent designed to work with all tuberculosis diagnostics while eliminating the need for cold chain. OM-S-treated sputum samples were assayed in several tests after multiday holds. Raw sputa from 100 patients underwent direct smear microscopy, were manually split and assigned to the OM-S group [OM-S added at collection (no other processing required) and tested after 0- to 5-day holds at room temperature] or standard-of-care (SOC) group (NaOH/N-acetyl l-cysteine decontamination, all tested on day of collection). Concentrated smear microscopy, Lowenstein Jensen (LJ) culture, and mycobacteria growth indicator tube (MGIT) culture were performed. For patients with negative direct smear, a second sample was split, with SOC (raw sputum) and OM-S portions (sediment) tested in the Xpert MTB/RIF (Xpert) assay. OM-S group and SOC group results were strongly concordant on all four tests [range, 89% (MGIT)-97% (Xpert)]. OM-S MGIT, LJ, and Xpert tests were in statistical agreement with SOC MGIT as reference. OM-S specimens had lower culture contamination rates (3% vs. 10% LJ; 2% vs. 5% MGIT) but required, on average, 5.6 additional days to become MGIT-positive. The findings suggest that samples held/transported in OM-S are compatible with smear microscopy, LJ or MGIT culture, and Xpert, and perform comparably to fresh sputum samples. Larger feasibility studies are warranted.